An overview on the teleost bone mechanophysiology. (2nd March 2018) - Cardeira, J.; Laizé, V.; Martins, G.; Cancela, M. L.; Gavaia, P. J.
Summary: Vertebrate tissues are plastic and actively adapt to the mechanical environment. Teleost bone, despite differences with its mammalian counterpart, also responds to mechanical loading, evidencing the presence of a functional mechanosensing system. Deformities such as spinal curvatures and vertebral compressions can result in internal loading disturbances. On the other hand, the external mechanical loading can be modulated by controlling gravity (i.e. inducing micro‐ or hyper‐gravity) or swimming conditions. There is an increasing interest in understanding teleost bone mechanobiology resulting from the current importance of teleosts as aquaculture resources and as biomedical models. Thus, this paper aims at reviewing relevant data that contribute to understanding fundamental questions, such as how teleost bone recognizes the biomechanical environment and how it phenotypically responds to specific mechanical changes. Particularly relevant for research purposes, technological and technical aspects of one of the most used loading‐induced systems, the swimming exercise, are also presented.